Adipogenesis and WNT signalling. - Christodoulides, C; Lagathu, C; Sethi, J; Vidal-Puig, A (2009)
An inability of adipose tissue to expand consequent to exhausted capacity to recruit new adipocytes might underlie the association between obesity and insulin resistance. Adipocytes arise from mesenchymal precursors whose commitment and differentiation along the adipocytic lineage is tightly regulated. These regulatory factors mediate cross-talk between adipose cells, ensuring that adipocyte growth and differentiation are coupled to energy storage demands. The WNT family of autocrine and paracrine growth factors regulates adult tissue maintenance and remodelling and, consequently, is well suited to mediate adipose cell communication. Indeed, several recent reports, summarized in this review, implicate WNT signalling in regulating adipogenesis. Manipulating the WNT pathway to alter adipose cellular makeup, therefore, constitutes an attractive drug-development target to combat obesity-associated metabolic complications.